Patient Specific Titanium Implant Post Maxillectomy: The Evolution of Surgical Reconstruction - Jeeven Velayutham; Liew Yew Toong; Sakina Ghauth (Sumatera Medical Journal, 2026)
Background: Malignancies arising from paranasal sinus account for 0.2-0.8% of all malignant neoplasms and 3% of the malignant neoplasms occurring in the head and neck. Surgical treatment of maxillary sinus carcinoma often consists of an open sub-total or total maxillectomy with a subsequent significant defect. Besides, the proximity of the maxillary sinus with complex anatomical structures make reconstruction a major challenge for head and neck surgeons. Reconstruction with temporalis myofascial flap along with titanium implant have proven to be a reliable reconstruction technique. Objective:The objective of this case report is to highlight our surgical management and reconstruction method for maxillary sinus cancer. Methods: We present a case of maxillary sinus squamous cell carcinoma in a 69 years old patient, who underwent total maxillectomy and reconstruction of surgical defect with 3D printed patient specific titanium implant and temporalis myofascial flap. Results: The patient had adequate postoperative functional and aesthetic outcome. The objective of this case report is to highlight our surgical management and reconstruction method for maxillary sinus cancer. Conclusion: The reconstruction method brings reliable and satisfactory functional result and quality of life with minimal complications.